The impact of Industry 4.0 on the processes of social innovation - Sándor Karajz (Theory, Methodology, Practice, 2021)
Our previous research into this topic has proved that technical developments significantly affect processes and effectiveness of social innovation. The current process of this development is called Industry 4.0. The first part of the study deals with industrial evolutions and the process of Industry 4.0 is interpreted. The second part of the study presents national and international examples and good practices in order to examine the relationship between digitalisation and social innovation. The results of Industry 4.0 reveal that there is an increasing number of solutions for social innovation that are based on digitalisation and automation. The current digital revolution is radically changing societies and opening up new opportunities for social innovation. Industry 4.0 results in social innovation solutions that use artificial intelligence to improve and optimise processes.